Dimensions of normativity : new essays on metaethics and jurisprudence - Plunkett, David; Shapiro, Scott; Toh, Kevin (New York, NY : Oxford University Press, 2019)
This text collects together new essays by moral and legal philosophers that are aimed at knocking down a disciplinary wall that divides contemporary philosophical thinking about the nature of morality and contemporary philosophical thinking about the nature of law.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 10, 2019).
Keywords: Law -- Philosophy; Jurisprudence; Normativity (Ethics); Law -- Moral and ethical aspects; Metaethics; Law; Jurisprudence & general issues